Psychosocial Status of Liver Transplant Candidates in Iran and Its Correlation with Health-Related Quality of Life and Depression and Anxiety - Maryam Banihashemi; Mohsen Hafezi; Mohsen Nasiri-Toosi; Ali Jafarian; Mohammad Reza Abbasi; Mohammad Arbabi; Maryam Abdi; Mahzad Khavarian; Ali-Akbar Nejatisafa (Journal of Transplantation)
Objectives. The study was aimed at providing a psychosocial profile for Iranian liver transplant candidates referred to an established liver transplantation program. Material and Methods. Patients assessed for liver transplant candidacy in Imam Khomeini Hospital (Tehran, Iran) between March 2013 and September 2014 were included. The following battery of tests were administered: Psychosocial Assessment of Candidates for Transplant (PACT), the Short-Form health survey (SF-36), and Hospital Anxiety and Depression Scale (HADS). Results. Psychosocial assessment in 205 liver transplant candidates revealed significant impairments in several SF-36 domains; social functioning was the least and physical functioning was the most impaired domains. The prevalence of cases with probable anxiety and depressive disorders, according to HADS, was 13.8% and 5.6%, respectively. According to PACT, 24.3% of the assessed individuals were considered good or excellent candidates. In 11.2%, transplantation seemed poor candidate due to at least one major psychosocial or lifestyle risk factor. Poor candidate quality was associated with impaired health-related quality of life and higher scores on anxiety and depression scales (p<0.05). Conclusions. Transplant programs could implement specific intervention programs based on normative databases to address the psychosocial issues in patients in order to improve patient care, quality of life, and transplant outcomes.